Decent Work: A Psychological Perspective - Blustein, David L.; Olle, Chad; Connors-Kellgren, Alice; Diamonti, A. J. (Frontiers in Psychology, 2016)
This contribution, which serves as the lead article for the Research Section entitled “From Meaning of Working to Meaningful Lives: The Challenges of Expanding Decent Work”, explores current challenges in the development and operationalization of decent work. Based on an initiative from the International Labor Organization (ILO; 1999), decent work represents an aspirational statement about the quality of work that should be available to all people who seek to work around the globe. Within recent years, several critiques have been raised about decent work from various disciplines, highlighting concerns about a retreat from the social justice ethos that had initially defined the concept. In addition, other scholars have observed that decent work has not included a focus on the role of meaning and purpose at work. To address these concerns, we propose that a psychological perspective can help to revitalize the decent work agenda by infusing a more specific focus on individual experiences and by reconnecting decent work to its social justice origins. As an illustration of the advantages of a psychological perspective, we explore the rise of precarious work and also connect the decent work agenda to the Psychology-of-Working Framework and Theory (Blustein, 2006; Duffy, Blustein, Diemer, and Autin, in press).